A displacement measurement system based on optical triangulation method - 付献斌 刘彬 张玉存 (Optoelectronics letters, 2011)
A new displacement measurement system is described in this paper according to the basic principles of traditional laser triangulation method. The range of the traditional measuring method is enlarged by measuring in sections. Three independent CCDs, which are distributed uniformly along the optical axis, are used to achieve subsection measurement. The plane mirror is regarded as a virtual detector. When imaging beam is reflected by the plane mirror, the beam is imaged on the CCD. The designed system is equivalent to add a CCD. The feasibility of the displacement measurement system is verified by the experiment.